Rereading Nightlife Policy: From Social Regulation to the Reality of Prostitution - Imran, Muhammad; Fathia Bailusy, Ummi Suci; Fichriyadi Hastira, Muh; Astuti, Widya; Mujiburrahman (Palita: Journal of Social Religion Research, 2025)
This study discusses the dynamics of nightlife tax policy in Makassar City, particularly in the Nusantara Street area, which is known as a center of nightlife activities and a location for covert prostitution. Using a descriptive qualitative approach, this study examines how Local Regulation No. 1 of 2024, which stipulates a 75% increase in nightlife tax, functions not only as a fiscal instrument to increase Local Own-Source Revenue (PAD), but also as a social regulatory instrument. The results of the study show that this policy has dual implications: on the one hand, it strengthens the political legitimacy of the city government in responding to the moral demands of the community, but on the other hand, it gives rise to unexpected consequences in the form of new negotiations between the government, nightlife entrepreneurs, and sex workers. High taxes actually encourage the capitalization of sex workers' bodies, widen the economic dependence of the surrounding community on the nightlife industry, and open up space for informal political compromise between entrepreneurs and officials. This study confirms that fiscal policy is never neutral, but is always linked to local social, political, and economic dynamics. The necessary follow-up is strengthening alternative policies based on a humanistic and inclusive approach, such as providing formal employment, economic empowerment programs for women, and more transparent and accountable supervision. Keywords: Nightlife tax, prostitution, fiscal policy, social regulation